Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4103/0253-7613.106437
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histopathological effects on liver due to acute oral toxicity of aqueous leaf extract of Ecliptaalba on female Swiss albino mice

Abstract: Background:Limited data is available about the toxicity of herbal remedies used for self-medication. Since a popular medicinal plant Ecliptaalba contains various bioactive molecules, the present study aimed to observe the biochemical and histological changes in liver associated with acute oral toxicity (LD50) of aqueous extract of E. alba (L.) Hassk. in female Swiss albino mice.Materials and Methods:For the acute oral toxicity study, the animals were divided into six groups of 6 mice each. Group– I was normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 7 publications
4
25
0
1
Order By: Relevance
“…Mossoba et al [33], in a study of cell and mitochondrial function in human cells of the proximal tubule of the kidney (HK-2), reported elevated levels of nephrotoxicity biomarkers in C. ternifolia. Singh et al [34], in studies of E. alba of the family Astereaceae, which contains flavonoids, reported similar results in the liver with adverse biochemical and histological effects at a concentration of 2,500 mg/kg. ey observed that the oral administration of an aqueous extract of E. alba in female rats produced harmful effects on biochemical parameters and increased transaminase levels after liver damage due to induced membrane permeability; in a similar study alteration was found [33].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Mossoba et al [33], in a study of cell and mitochondrial function in human cells of the proximal tubule of the kidney (HK-2), reported elevated levels of nephrotoxicity biomarkers in C. ternifolia. Singh et al [34], in studies of E. alba of the family Astereaceae, which contains flavonoids, reported similar results in the liver with adverse biochemical and histological effects at a concentration of 2,500 mg/kg. ey observed that the oral administration of an aqueous extract of E. alba in female rats produced harmful effects on biochemical parameters and increased transaminase levels after liver damage due to induced membrane permeability; in a similar study alteration was found [33].…”
Section: Discussionmentioning
confidence: 66%
“…ey observed that the oral administration of an aqueous extract of E. alba in female rats produced harmful effects on biochemical parameters and increased transaminase levels after liver damage due to induced membrane permeability; in a similar study alteration was found [33]. Later, the same author evaluated the aqueous extract of Phyllanthus niruri leaves and found liver damage at greater doses [35]. e group of enzymes that metabolize xenobiotics are called P450 cytochromes (CYPs), in particular, the enzyme CYP3A4.…”
Section: Discussionmentioning
confidence: 90%
“…This data was in partial harmony with Sun et al, (2014) who declared significant elevation in liver enzymes while albumin and relative hepatic weights were not affected. The levels of ALP, ALT and albumin had been used as valuable indicators for hepatic function (Singh et al, 2013;Wang et al, 2003;Wu et al, 2014). The liver enzymes proposed to be bound by the cell membrane of hepatic cells inside the hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…16 Body weight and organ weight are important factors to monitor the health of an individual and to analyze the toxic impact of herbal plant extracts. 17 Loss in body weight is frequently the first indicator of the onset of an adverse effect. A dose, which causes 10% or more reduction in the body weight, is considered to be a toxic dose.…”
Section: Discussionmentioning
confidence: 99%